Mitochondrial General Control of Amino Acid Synthesis 5 Like 1 Regulates Glutaminolysis, Mammalian Target of Rapamycin Complex 1 Activity, and Murine Liver Regeneration. Issue 2 (17th October 2019) - Wang, Lingdi; Zhu, Lu; Wu, Kaiyuan; Chen, Yong; Lee, Duck‐Yeon; Gucek, Marjan; Sack, Michael N.
Abstract : Background and Aims: The regenerative capacity of the liver plays a protective role against hepatotoxins and impaired regeneration exacerbates liver dysfunction in nonalcoholic fatty liver disease (NAFLD). Mitochondrial bioenergetic and ‐synthetic functions are important contributory factors in hepatic regeneration, and the control of mitochondrial protein acetylation is implicated in the mitochondrial susceptibility to liver stressors. Here, we evaluated the role of general control of amino acid synthesis 5 like 1 (GCN5L1), a mediator of mitochondrial metabolism and acetylation, in modulating murine liver regeneration (LR) in response to acute CCl4 ‐induced hepatotoxicity. Approach and Results: Initial metabolomic screening found that liver GCN5L1 knockout (LKO) mice have augmented glutaminolysis. Absence of GCN5L1 modified enzyme activity of liver‐enriched glutaminase enzyme (glutaminase 2; GLS2), and GCN5L1 levels modulated GLS2 oligomerization and acetylation. This metabolic remodeling resulted in the elevation of α‐ketoglutarate levels, which are known to activate mammalian target of rapamycin complex 1 (mTORC1). This signaling pathway was induced with increased phosphorylation of S6 kinase in LKO hepatocytes, and inhibition of glutaminolysis reversed aberrant mTORC1 signaling. At the same time, glutaminolysis, activity of GLS2, and activation of mTORC1 signaling were reversed by the genetic reintroduction of the mitochondrial isoform of GCN5L1 into LKO primary hepatocytes. Finally, LKO mice had a more robust regenerative capacity in response to CCl4 hepatoxicity, and this response was blunted by both the mTORC1 inhibitor, rapamycin, and by pharmacological blunting of glutaminolysis. Conclusions: These data point to a central role of glutaminolysis in modulating the regenerative capacity in the liver. Furthermore, inhibition of mitochondrial GCN5L1 to augment LR may be a useful strategy in disease states linked to hepatotoxicity.